A laboratory study analysis of the cyclic fatigue strength of glide path instruments at simulated body temperature (Giornale Italiano di Endodonzia, 2022)
Aim: This study aimed to evaluate the cyclic flexural fatigue resistance of four glide path files (one rotary and three reciprocating) by using a simulated root canal model.Method: 25-mm-length files (n=10) (ProGlider, Dentsply Maillefer; X1-Glide Path, MK Life; WaveOne Gold Glider, Dentsply Maillefer; and R-Pilot, VDW) were mounted in a 6:1 reduction handpiece powered by a torque-controlled motor and introduced into a 1.4-mm-diameter and 19-mm-length stainless steel tube (9-mm-length curved segment with an 86-degree curvature angle. The files were worked under irrigation with 37 °C distilled water until visual and/or audible observation of fracture. The time to each file fracture was measured with aid of a digital stopwatch. X1-Glide Path, WaveOne Gold Glider, and R-Pilot files were subjected to reciprocating motion while ProGlider files were subjected to continuous 300-rpm clockwise rotation. The surface morphology of two specimens per group was observed under scanning electron microscopy before and after fatigue testing. The file types were compared using one-way ANOVA and posthoc Tukey (p WaveOne Gold Glider (235.65 sec) > ProGlider files (158.30 sec). The Weibull analysis confirmed that ProGlider and X1-Glide Path files are associated with the shortest and the longest mean time to failure, respectively.Conclusion: X1-Glide Path files showed significantly higher cyclic flexural fatigue resistance than other file types.